Constructing Narratives: Indonesia-Australia Relations in Indonesian History Textbooks - Wawan Darmawan; Annisa'a Ambarnis; Andromeda Aderoben; Wildan Insan Fauzi (Paramita: Historical Studies Journal, 2025)
Abstract: This study aims to analyze how Australian history is represented in Indonesian history textbooks and how these narratives have evolved. Specifically, it examines the differences in the portrayal of Australian history in high school history textbooks published during the New Order government (1966-1998) and the Reformasi government (1999-2023). To achieve this objective, this study employs the critical discourse analysis method, which allows for systematically examining communication symbols embedded in historical narratives. This approach enables a deeper understanding of how historical events are framed and contextualized in Indonesian history textbooks. The findings reveal that during the New Order period (1966-1998), Australian history was primarily linked to Indonesia’s independence struggle (1945-1949) and the Guided Democracy period (1959-1965). During this time, Australia was depicted as a nation that supported Indonesia’s independence. However, in the Reformasi era (post-1999), significant changes emerged in the historical narrative, particularly in depicting Australia’s involvement in the East Timor referendum. Textbooks published after 1999 reflect a more complex relationship, highlighting Australia’s role in East Timor’s separation from Indonesia. These findings indicate that the representation of history in textbooks is influenced by political dynamics and diplomatic relations between the two nations. The shift in historical narratives demonstrates how government policies and national discourse shape students' collective understanding of international history. Therefore, the history curriculum must adopt a more critical and balanced approach to avoid being solely shaped by political interests. This study confirms that historical narratives in textbooks are not static but are shaped by contemporary political contexts and bilateral relations. Abstrak: Penelitian ini bertujuan untuk menganalisis bagaimana sejarah Australia direpresentasikan dalam buku teks sejarah Indonesia serta bagaimana narasi tersebut berkembang dari waktu ke waktu., khususnya yang diterbitkan pada masa pemerintahan Orde Baru (1966–1998) dan masa Reformasi (1999–2023). Untuk mencapai tujuan tersebut, penelitian ini menggunakan metode critical discourse analysis (analisis wacana kritis) yang memungkinkan penelusuran sistematis terhadap simbol-simbol komunikasi yang terkandung dalam narasi sejarah. Hasil penelitian menunjukkan bahwa pada masa Orde Baru, sejarah Australia umumnya dikaitkan dengan perjuangan kemerdekaan Indonesia (1945–1949) dan masa Demokrasi Terpimpin (1959–1965), di mana Australia digambarkan sebagai negara yang mendukung kemerdekaan Indonesia. Namun, pada masa Reformasi (pasca-1999), narasi sejarah mengalami perubahan signifikan, terutama terkait peran Australia dalam proses referendum Timor Timur. Buku-buku teks yang diterbitkan setelah 1999 menunjukkan hubungan yang lebih kompleks, dengan menyoroti peran Australia dalam pemisahan Timor Timur dari Indonesia. Temuan ini menunjukkan bahwa representasi sejarah dalam buku teks sangat dipengaruhi oleh dinamika politik dan hubungan diplomatik kedua negara. Perubahan narasi mencerminkan bagaimana kebijakan pemerintah dan wacana nasional membentuk pemahaman kolektif siswa terhadap sejarah internasional. Oleh karena itu, kurikulum sejarah perlu diarahkan pada pendekatan yang lebih kritis dan seimbang agar tidak didominasi oleh kepentingan politik semata. Studi ini menegaskan bahwa narasi sejarah dalam buku teks bersifat dinamis dan sangat dipengaruhi oleh konteks politik serta hubungan bilateral yang sedang berlangsung.